Clinical evaluation of two pediatric rotary systems versus a conventional system for pulpectomy of primary mandibular molars: A single blind randomized clinical trial - Redhu, Monika; Dalal, Rashmi; Neetika, Neetika; Garg, Shalini; Srivastava, Ankit; Gupta, Anil (Journal of Neonatal Surgery, 2025)
Objectives: The objective was to evaluate the efficacy of paediatric rotary system Kedo-S file and Neoendopedoflex file with conventional system in pulpectomy of primary mandibular molars in term of instrumentation time, procedural errors, obturation quality and post-operative pain. Materials and method: 45 primary mandibular molars indicated for pulpectomy in 4-8 years old children were randomly assigned into three groups (n=15). Group I was instrumented using K-hand files, Group II with Kedo-S rotary file and Group III with Neoendopedoflex file. Standardized radiographs were taken before and after instrumentation. Root canal preparation time was recorded using stopwatch. Statistical analysis of the obtained data was done using SPSS Software version 20. Results: Instrumentation time was significantly less with rotary system when compared to manual system (P=0.00). In term of procedural errors 30% cases of stripping and 10% cases of instrument fracture were observed in Kedo-S group. Higher number of over obturation were seen with Kedo-S file (30%) and under obturation was observed with K-file (18.2%) and 9.1% cases were observed in Neoendopedoflexgroup. Under-obturation was observed more in K -file than that of Neoendopedoflex file. Stripping was noticed in 30% cases and instrument fracture in 10% cases in Kedo-S group. However, no significant difference was observed among rotary system and conventional hand file system for procedural error and quality of obturation. Significant difference was noted among three groups with respect to post operative pain at 24 hours (P value=0.05). Conclusion : The present study demonstrates that Neoendopedoflex rotary system performed overall better in term of procedural errors, quality of obturation and post-operative pain followed by Kedo-S file and manual K file